Comparison of two skin protection regimes for the Prevention of Incontinence-associated Dermatitis in geriatric care (PID): a study protocol for an exploratory randomised controlled pragmatic trial - Jan Kottner; Monira El Genedy-Kalyoncu; Alexandra Fastner; Bettina Völzer; Kathrin Raeder; Konrad Neumann; Nils Axel Lahmann (BMJ Open)
Introduction The majority of aged long-term care receivers and patients in geriatric acute care are affected by some form of incontinence. These individuals are at risk of developing incontinence-associated dermatitis (IAD), a common type of irritant contact dermatitis caused by repeated and prolonged direct contact of the skin with urine and stool. The prevalence of IAD in these settings is high. Preventive measures include mild skin cleansing and the application of skin protecting leave-on products. Available evidence is weak regarding the comparative performance of different skin protection strategies and products due to a lack of confirmatory trials using relevant comparators and endpoints. Therefore, the overall aim of this exploratory trial is to compare the effects of three skin protection strategies to estimate effect sizes of the recently published core outcomes in IAD research.Methods and analysis A pragmatic three-arm, assessor-blinded, randomised controlled, exploratory trial with parallel group design will be performed, comparing film-forming and lipophilic skin protecting leave-on products for IAD prevention with standard incontinence care alone. The trial will be conducted in geriatric nursing homes and geriatric acute care settings in the federal state of Berlin, Germany. A total of n=210 participants being incontinent of urine and stool will be included. Outcomes include IAD incidence, erythema, erosion, maceration, IAD-related pain, patient satisfaction, safety, feasibility and compliance. IAD incidence of the control and intervention groups will be compared to estimate effect sizes, and the procedural feasibility of the intervention will be tested to plan a possible subsequent confirmatory randomised controlled trial.Ethics and dissemination The study received the approval of the ethics committee of Charité–Universitätsmedizin Berlin (EA4/043/22). Results will be disseminated through peer-reviewed open-access journals and international conferences.Trial registration number ClinicalTrials.gov (NCT05403762) and German Clinical Trials Register (Deutsches Register Klinischer Studien, or DRKS) (DRKS00028954).